Carborane‐Induced Excimer Emission of Severely Twisted Bis‐o‐Carboranyl Chrysene. Issue 33 (12th July 2018) - Marsh, Adam V.; Cheetham, Nathan J.; Little, Mark; Dyson, Matthew; White, Andrew J. P.; Beavis, Peter; Warriner, Colin N.; Swain, Anthony C.; Stavrinou, Paul N.; Heeney, Martin
Abstract: The synthesis of a highly twisted chrysene derivative incorporating two electron deficient o ‐carboranyl groups is reported. The molecule exhibits a complex, excitation‐dependent photoluminescence, including aggregation‐induced emission (AIE) with good quantum efficiency and an exceptionally long singlet excited state lifetime. Through a combination of detailed optical studies and theoretical calculations, the excited state species are identified, including an unusual excimer induced by the presence of o ‐carborane. This is the first time that o ‐carborane has been shown to induce excimer formation ab initio, as well as the first observation of excimer emission by a chrysene‐based small molecule in solution. Bis‐ o ‐carboranyl chrysene is thus an initial member of a new family of o ‐carboranyl phenacenes exhibiting a novel architecture for highly‐efficient multi‐luminescent fluorophores. Abstract : Can carboranes induce excimers? Incorporation of o ‐carborane into chrysene causes severe deformation of the aromatic backbone and, accordingly, restricted rotation of the carborane. This unusual geometry leads to localized (LE), aggregation‐induced (AIE), and excimer emission. The latter is the first example of a carborane electronically involved in an excimer species.